2018
DOI: 10.1016/j.heliyon.2018.e01056
|View full text |Cite
|
Sign up to set email alerts
|

Three-rods test as drivers' license vision test from the viewpoint of reproducibility, eye deviation, and functional visual acuity

Abstract: BackgroundThree-rods test is required as depth perception vision test to obtain motor vehicle license to drive taxies, buses, and trucks in Japan. Functional visual acuity is measured automatically by successive visual target presentation in a fixed period of time. This study examined three-rods test from the viewpoint of reproducibility, eye deviation, and functional visual acuity to assess the feasibility for drivers' license vision test.MethodsAt three-rods test, a central rod was moved at the speed of 50 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Regarding the validity of the three-rods test, Matsuo et al previously reported that this test was reproducible and feasible enough for an appropriate screening test of depth perception in the general population, although it is not as accurate as stereo tests used in an ophthalmic practice [7]. The authors also reported that the three-rods test had a better correlation with functional VA tested with both eyes open [6]. Similarly, we also find a relationship between binocular distance functional VA and performance on the modified three-rods test employed in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the validity of the three-rods test, Matsuo et al previously reported that this test was reproducible and feasible enough for an appropriate screening test of depth perception in the general population, although it is not as accurate as stereo tests used in an ophthalmic practice [7]. The authors also reported that the three-rods test had a better correlation with functional VA tested with both eyes open [6]. Similarly, we also find a relationship between binocular distance functional VA and performance on the modified three-rods test employed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The design and structure of the system were basically the same as the three-rods test used previously [ 6 ]. Due to the viewing distance being greater than in the standard three-rods test, the apparatus was scaled up in size so that it would have the same optical size (at a maximal distance of 20 m) as the apparatus in the standard three-rods test.…”
Section: Participants and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that the statistically signi cant positive correlation of results between threerods test and stereotests used in daily ophthalmic practice (distance Randot Stereotest and Titmus Stereotest) 16 . The authors also reported that the results of the three-rods test done on separate days were positively correlated 17 . These studies collectively support the validity of the use of the three-rods test as a means of evaluating binocular stereoacuity.…”
Section: Introductionmentioning
confidence: 91%